ВИКОРИСТAННЯ ПРИРОДНИЧО-КРAЄЗНAВЧИХ МAТEРIAЛIВ НA УРОКAХ ГEОГРAФIЇ У 6 КЛAСI - Тинку, Катерина Валеріївна (My University, 2024)
In the master's work, the role and significance of natural and local history materials in geography lessons and the methodology of researching natural and local history materials were investigated. It examines the historical and geological geomorphological, hydrological, and biogenic components of the city of Hertsa. The general characteristics of the landscape structure and the landscape structure of the city territory were analyzed. Anthropogenic landscapes of the city territory were studied, namely: frame, background, point, humanistic landscapes. The natural and local history materials were processed in geography lessons for the 6th grade, and lesson plans for the 6th grade were developed.